Rencana Aksi Pengembangan Usaha Koperasi Kelurahan Merah Putih Kecamatan Genteng Kota Surabaya - Iswara, Ulfah Setia; Palupi, Dian; Suwitho, Suwitho; Setyabudi, Teguh Gunawan; Kurnia, Kurnia (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to provide training in designing business development action plans for the Merah Putih Village Cooperative (KKMP) in Genteng District, Surabaya City. This community service activity was conducted in five KKMPs in Genteng District: Embong Kaliasin Village, Genteng Village, Kapasari Village, Ketabang Village, and Peneleh Village, by 2025. Genteng District is located in the center of Surabaya City. The community service activity began with problem identification, training and mentoring, as well as monitoring and evaluation. The results indicated that cooperative management still faces obstacles in aspects of membership, business premises utilization, and determining appropriate business types. Through training and mentoring, each KKMP successfully identified local business potential and developed a cooperative work program action plan for the coming year. This activity increased cooperative managers' understanding of regional potential-based business development strategies and encouraged the strengthening of cooperatives' role in community economic empowerment. The business development action plan was implemented by identifying business potential in each KKMP and developing a work program plan for the coming year.